A lightweight identity-based Rivest-Shamir-Adleman authentication scheme for mobile ad hoc networks [electronic resource] - 300604 Tameem Eissa; Shukor Abd. Razak, supervisor; Md. Asri Ngadi; Fakulti Sains Komputer dan Sistem Maklumat (2011)
Thesis (Ph.D (Sains Komputer)) - Universiti Teknologi Malaysia, 2011